Morbidity and Mortality Caused by Noncompliance With California Hospital Licensure: Immediate Jeopardies in California Hospitals, 2007–2017. Issue 2 (11th March 2022) - Zheng, Micha Y.; Lui, Hansen; Patino, German; Mmonu, Nnenaya; Cohen, Andrew J.; Breyer, Benjamin N.
Abstract : Objective: The California Department of Public Health investigates compliance with hospital licensure and issues an administrative penalty when there is an immediate jeopardy. Immediate jeopardies are situations in which a hospital's noncompliance of licensure requirements causes serious injury or death to patient. In this study, we critically examine immediate jeopardies between 2007 and 2017 in California. Methods: All immediate jeopardies reported between 2007 and 2017 were abstracted for hospital, location, date, details of noncompliance, and patient's health outcome. Results: Of 385 unique immediate jeopardies, 141 (36.6%) caused mortality, 120 (31.2%) caused morbidity, 96 (24.9%) led to a second surgery, 9 (2.3%) caused emotional trauma without physical trauma, and 19 (4.9%) were caught before patients were harmed. Immediate jeopardy categories included the following: surgical (34.2%), medication (18.9%), monitoring (14.2%), falls (7.8%), equipment (5.4%), procedural (5.4%), resuscitation (4.4%), suicide (3.9%), MD/RN miscommunication (3.4%), and abuse (2.3%). Conclusions: Noncompliance to hospital licensure causes significant morbidity and mortality. Statewide hospital licensure policies should focus on enacting standardized reporting requirements of immediate jeopardies into an Internet-based form that public health officials can regularly analyze to improve hospital safety.